A Study Of Bio-Oil Derived From Rice Husk Using Pyrolysis As A Potential Gasoline Additive (Journal of Renewable Energy and Mechanics, 2025)
Biomass energy is an alternative solution for reducing emissions compared to traditional energy sources because biomass is a carbon-neutral resource. In this study, rice husk biomass was processed using pyrolysis technology at temperatures of 250°C, 300°C, and 350°C, with retention times of 60 and 90 minutes. The crude pyrolytic oil was then refined through a distillation process to improve its quality, followed by chemical and physical composition tests. The results showed that the highest yield of crude pyrolytic oil was obtained at a temperature of 300°C with a retention time of 90 minutes. The distillation process produced oil with more than 90% of its carbon chains in the gasoline range (C7-C11). Additionally, a high concentration of phenolic compounds was detected in the bio-oil, making it a viable option as a fuel additive. The bio-oil derived from rice husk waste had a calorific value of 1777.24 cal/gram, indicating its potential as a gasoline blend alternative fuel